Changes In The Dental Arch Due To Oblıgatory Early Extractıon Of Fırst Permanent Molars - Aslı Ender Telli; Serpil Aytan (Galenos Yayinevi, 1989)
The first permanent molars are the most frequently extracted teeth due to caries. Early loss of these teeth which are known as "the key of the occlusion" may lead to rotations, migrations, and alongations of the other teeth in the dental arches, and finally may cause occlusal disorders. This research is conducted on the patients whose first permanent molars need to be extracted due to profound caries and unrestorable material loss. By means of the lateral and panoramic radiographs taken just before the extraction and one year later, the local changes in the extraction and non-extraction segments are compared.